Taphonomic signature of Eurasian eagle owl (Bubo bubo) on fish remains - Guillaud, Emilie; Lebreton, Loïc; Béarez, Philippe (Folia Zoologica)
Fish bones are often found in Palaeolithic cave deposits, but the origin of their accumulation is generally poorly known. Knowledge of the accumulator is essential to understand the role of fish in human subsistence activities, and the Eurasian eagle owl (Bubo bubo) is frequently recognized as an accumulator of skeletal remains on archaeological sites. We analyzed 27 Eurasian eagle owl pellet samples from Tautavel (Pyrénées Orientales) in southern France. From this sample, we identified 1812 fish remains distributed across seven species: allis shad (Alosa alosa), European eel (Anguilla Anguilla), gudgeon (Gobio gobio), roach (Rutilus rutilus), Mediterranean barbel (Barbus meridionalis), chub (Squalius cephalus) and tench (Tinca tinca). These remains were characterised by relatively complete skeletal representation, minimal bone fragmentation and low digestive surface damage. On the basis of surface modification, we produced a set of criteria to be applied to the fossil record in order to highlight the role of this owl in cave fish deposits.